Consumer reactions to potential intrusiveness and benefits of RFID. (14th January 2008) - Sill, Heather E.; Fisher, Sandra L.; Wasserman, Michael E.
The research conducted in this study examined the effect that information and personal traits have on potential consumers' intentions to purchase Radio Frequency Identification (RFID)-tagged products. An experiment was conducted involving 128 students at a small, private university. Participants in the study were provided with general information on RFID, as well as more specific information on the benefits and intrusiveness of the technology throughout the supply chain. Two personal characteristics, personal innovativeness and propensity to trust, were assessed. Intrusiveness and propensity to trust were found to be predictors of trust in RFID. Trust in RFID was, as hypothesised, a predictor of an individual's intention to purchase RFID-tagged products. The implications for firms planning to use RFID and future research opportunities are discussed.